Aplikasi Edible Coating Pati Sagu dengan Penguat Selulosa Bakterial Terhadap Karakteristik Buah Apel Potong - Agustin, Sukmiyati; Cahyanto, Muhammad N (AGRITEKNO: Jurnal Teknologi Pertanian, 2024)
Quality and shelf life degradation are problems in minimally processed horticultural products (fresh-cut). Edible coating is one way to protect the product from the quality degradation process. Edible coating is a thin layer of edible material applied to the product's surface. One of the potential materials for forming edible films is sago starch. Sago starch-based edible coating has the disadvantage of low mechanical strength and a barrier to water vapor. The addition of bacterial cellulose (BC) filler functions as a physical barrier to vapor and gas while improving its mechanical strength. The treatments applied to fresh-cut Malang apples were without edible coating, with sago edible coating and sago edible coating plus BC. The application of sago edible coating with the addition of BC was able to reduce changes in weight loss by up to 66.4%, and hardness by up to 32.50%, as well as maintaining the total dissolved solids, color (brightness), and acidity level (pH) of fresh-cut apples until the 8th day of storage. Adding BC to the edible coating formula provided a better protective effect than edible coating without BC.